Ruxolitinib therapy followed by reduced-intensity conditioning for hematopoietic cell transplantation for myelofibrosis: Myeloproliferative Disorders Research Consortium 114 study - Gupta, V; Kosiorek, H; Mead, A; Klisovic, R; Galvin, J; Berenzon, D; Yacoub, A; Viswabandya, A; Mesa, R; Goldberg, J; Price, L; Salama, M; et al. (Elsevier, 2018)
We evaluated the feasibility of ruxolitinib therapy followed by a reduced-intensity conditioning (RIC) regimen for patients with myelofibrosis (MF) undergoing transplantation in a 2-stage Simon phase II trial. The aims were to decrease the incidence of graft failure (GF) and nonrelapse mortality (NRM) compared with data from the previous Myeloproliferative Disorders Research Consortium 101 Study. The plan was to enroll 11 patients each in related donor (RD) and unrelated donor (URD) arms, with trial termination if ≥3 failures (GF or death by day +100 post-transplant) occurred in the RD arm or ≥6 failures occurred in the URD. A total of 21 patients were enrolled, including 7 in the RD arm and 14 in the URD arm. The RD arm did not meet the predetermined criteria for proceeding to stage II. Although the URD arm met the criteria for stage II, the study was terminated owing to poor accrual and a significant number of failures. In all 19 transplant recipients, ruxolitinib was tapered successfully without significant side effects, and 9 patients (47%) had a significant decrease in symptom burden. The cumulative incidences of GF, NRM, acute graft-versus-host disease (GVHD), and chronic GVHD at 24 months were 16%, 28%, 64%, and 76%, respectively. On an intention-to-treat basis, the 2-year overall survival was 61% for the RD arm and 70% for the URD arm. Ruxolitinib can be integrated as pretransplantation treatment for patients with MF, and a tapering strategy before transplantation is safe, allowing patients to commence conditioning therapy with a reduced symptom burden. However, GF and NRM remain significant.